Cognitive Penetration: Inference or Fabrication?. Issue 3 (3rd July 2021) - Teng, Lu
ABSTRACT: Cognitive penetrability refers to the possibility that perceptual experiences are influenced by our beliefs, expectations, emotions, or other personal-level mental states. In this paper, I focus on the epistemological implication of cognitive penetration, and examine how, exactly, aetiologies matter to the justificatory power of perceptual experiences. I examine a prominent theory, according to which some cognitively penetrated perceptual experiences are like conclusions of bad inferences. Whereas one version of this theory is psychologically implausible, the other version has sceptical consequences. In the second half of the paper, I suggest an alternative theory, drawing on recent empirical research on imagining-perception interaction and the epistemology of imagining.